Promoting equity on licensing exams: Test accommodations for medical students with diabetes - Lucia McGeehan; Melanie J. Robbins; Daniel Jurich; Sydney Tucker (PLoS ONE, 2026)
In this article, we will provide information about the USMLE test accommodations process and present data on requests based on diabetes, including the number of requests and the types of accommodations requested and approved. This study summarizes population-level data from 2023 on examinees who requested accommodations on the USMLE due to diabetes, the most prevalent physical impairment cited in requests at the time of this study. The data show that USMLE approves the vast majority of accommodation requests in full and all requests in part from examinees with diabetes. The average processing time is relatively low compared to the communicated 60-business day timeline, with less than 1.1% of cases exceeding this threshold and 42.1% approved in one business day. We conclude by addressing misconceptions that the process for requesting accommodations for individuals with diabetes is arduous and burdensome.